Interactive short-term effects of equivalent temperature and air pollution on human mortality in Berlin and Lisbon - Burkart, Katrin (2013)
There is substantial evidence that both temperature and air pollution are predictors of mortality. Thus far, few studies have focused on the potential interactive effects between the thermal environment and different measures of air pollution. Such interactions, however, are biologically plausible, as (extreme) temperature or increased air pollution might make individuals more susceptible to the effects of each respective predictor. This study investigated the interactive effects between equivalent temperature and air pollution (ozone and particulate matter) in Berlin (Germany) and Lisbon (Portugal) using different types of Poisson regression models. The findings suggest that interactive effects exist between air pollutants and equivalent temperature. Bivariate response surface models and generalised additive models (GAMs) including interaction terms showed an increased risk of mortality during periods of elevated equivalent temperatures and air pollution. Cold effects were mostly unaffected by air pollution. The study underscores the importance of air pollution control in mitigating heat effects.